Analysing the Role of Rail in Urban Freight Distribution - Katrien De Langhe (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Many different types of goods are transported to and delivered in cities, resulting in some urban freight challenges, such as increased vehicle movements within the city, collection of waste and one-way traffic flows towards the city. The growing urbanisation is expected to generate extra transport movements too. The European Transport White Paper states that national governments should try to implement policies to optimise freight transport in and around the city (European Commission, 2011). One option to do this is by using more sustainable transport modes. In that context, this research examines the potential role of rail in urban freight distribution, which was once important. Firstly, several existing cases of urban freight rail are discussed and compared. This results in the identification of success and failure factors. Secondly, a typology of cities and freight is set up. Thirdly, a conceptual cost model to estimate the potential of rail transport in urban freight distribution is proposed. The approach of this research consists of literature review and an expert meeting amongst academic and industry experts. The findings show that some relevant cases of urban freight rail exist in which different cities are involved. Knowledge of the different city and freight characteristics as well as the main success and failure factors is crucial. An appropriate methodology for assessing the potential of rail for urban freight distribution is a combination of stated and revealed preference and a social cost-benefit analysis.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; urban freight distribution; rail transport; city; social cost-benefit analysis